UPAYA PENINGKATAN KUALITAS KESEHATAN REPRODUKSI WUS MELALUI PENDIDIKAN KESEHATAN TENTANG KEPUTIHAN DI DESA TANGUNAN WILAYAH KERJA PUSKESMAS PURI KABUPATEN MOJOKERTO - Agustin Dwi Syalfina; Dian Irawati; Sari Priyanti; Wiwit Sulistyawati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Abstract Vaginal discharge is a white fluid that comes out of the burrow excessively. Vaginal discharge can be divided into several types including normal vaginal discharge (physiological) and abnormal vaginal discharge (pathological). Tangunan Village is located on Tangunan Highway, Puri District, Mojokerto Regency, and is guided by 1 village midwife and 1 village nurse. The background of the livelihood or occupation of the community in this village is the majority as farm laborers and entrepreneurs. The activity will be carried out starting from September 15, 2021 - January 15, 2022. Methods of Implementation In this community service activity, it is carried out in stages, namely surveying places in Tangunan village. The activity was carried out at the Tangunan Village hall. Before carrying out community service activities, the mothers were given questions about vaginal discharge and a post test was also carried out with the same questions. The results of the activity can be concluded that health education can increase participants' knowledge in understanding the material and increase attitudes about vaginal discharge. In accordance with the results of this community service, it is necessary to improve overall health promotion to the community according to the existing socio-culture in the community regarding knowledge, especially reproductive health problems, namely vaginal discharge.